AMF and EAMF: An Uncertain Future? - Shafiah F Muhibat (2017)
The ASEAN Maritime Forum and Expanded ASEAN Maritime Forum have been hailed as apt back-to-back venues for regional cooperation on maritime issues. Their future, however, is now uncertain.